Program Edukasi Covid-19 dan Pengenalan Aksara Lontara Kepada Siswa Mts Guppi di Desa Possi Tanah, Kecamatan Kajang, Kabupaten Bulukumba - Iqbal; Mukrimin; jabul reski, fadhil (Abdi Techno, 2021)
Community service programs are the practice of science, technology and art (IPTEKS) institutionalized by higher education through direct scientific methods to people who need to succeed in development and human development. Thematic Community service program (Thematic KKN) based on Problem Solving to solve problems with certain themes so that student activities are focused on solving certain problems and to achieve certain targets. One of them is the 105th Thematic KKN "Behavior Change Ambassador for Covid-19 Prevention and Participatory Oversight in the 2020 Pilkada". The Covid-19 thematic KKN is a Community Service Program to form concern in empowering and educating the public to prevent the spread of Coronavirus Disease 19 (Covid 19) while adhering to the Covid-19 health protocol, namely maintaining physical distance (Physical Distancing) and wearing masks . Students who take part in the Community service program are guided by Community service Lecturers (DPK) who process mentoring and monitoring using an online system. This service program through Thematic KKN is carried out using the during and offline service methods. The Community service program (KKN) is implemented in Bonto Loe Village, which is the area of ​​origin of students and this is done to minimize the spread of Covid-19. Work programs have posters about Aksara Lontarak and posters about Covid-19. On the other hand, there has been an increase in community compliance with health protocols by always wearing a mask when leaving the house.